Molecular Surveillance of Neoehrlichia mikurensis and Anaplasma phagocytophilum in Ticks from Urbanized Areas of Lithuania - Justina Snegiriovaitė; Indrė Lipatova; Miglė Razgūnaitė; Algimantas Paulauskas; Jana Radzijevskaja (Pathogens, 2025)
Neoehrlichia mikurensis and Anaplasma phagocytophilum, both members of the Anaplasmataceae family, are pathogens that can cause diseases in animals and humans. Ixodid ticks are the primary vectors for both species. While urban green spaces offer various ecological and social benefits, there is increasing evidence suggesting potential public health risks, particularly increased exposure to vector-borne diseases. The aim of the present study was to assess the prevalence and co-occurrence of A. phagocytophilum and N. mikurensis in ticks from urban environments in Lithuania. A total of 3599 Ixodes ricinus and 29 Dermacentor reticulatus were collected from 31 urban and 21 peri-urban areas. Ticks were examined for pathogens using duplex real-time PCR. Anaplasma phagocytophilum was detected in 4.47% of tested ticks, while N. mikurensis in 6.17%. Co-infection was found in 0.42% of I. ricinus specimens. Phylogenetic analysis of the groEl gene revealed low genetic variability of N. mikurensis and the circulation of two ecotypes (I and II) of A. phagocytophilum. Additionally, Ehrlichia muris was identified in I. ricinus ticks. This study is the first report of N. mikurensis detection in ticks from Lithuania. Our findings highlight the potential risk posed by tick-borne pathogens in urban and peri-urban areas of the country.